2017
DOI: 10.3390/polym9020045
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Confirmation of the Quinone Methide Hypothesis for the Condensation Reactions in Phenol-Formaldehyde Resin Synthesis

Abstract: Abstract:The mechanisms for the base-catalyzed condensation reactions in phenol-formaldehyde resin synthesis were investigated by using the density functional theory method. The structures of the intermediates and transition states, as well as the potential energy barriers of the involved reactions, were obtained. The hypothesis of quinine methide (QM) formation was theoretically confirmed. Two mechanisms were identified for QM formation, namely E1cb (elimination unimolecular conjugate base) and water-aided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Obviously, the hydrogen bonding effect suppresses the leaving of an OH ion and the relative bonding strength is the key factor that determines the relative reactivity for HMRAs to form quinonemethide intermediates. In our calculations for PF reactions [18], such effect was also found. In addition, the quinonemethides, 2-QM, 4-QM, and 6-QM are different in stability.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…Obviously, the hydrogen bonding effect suppresses the leaving of an OH ion and the relative bonding strength is the key factor that determines the relative reactivity for HMRAs to form quinonemethide intermediates. In our calculations for PF reactions [18], such effect was also found. In addition, the quinonemethides, 2-QM, 4-QM, and 6-QM are different in stability.…”
Section: Resultssupporting
confidence: 61%
“…Slower hydroxymethylation is not definitely in accordance with slower condensation reactivity. Theoretical calculations on PF reactions revealed that quinonemethide formation is the rate-determining step in the overall condensation reaction, and formation of para quinonemethide is faster than the formation of ortho quinonemethide [18]. This explained the experimental results that ortho - ortho -methylene linkage was always observed to be minor in comparison with ortho - para - and para - para -methylene linkages.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations